Analysis of physical processes in eruptive YSOs with near-infrared spectra and multiwavelength light curves. Issue 1 (26th March 2021) - Guo (郭震), Zhen; Lucas, P W; Contreras Peña, C; Smith, L C; Morris, C; Kurtev, R G; Borissova, J; Alonso-García, J; Minniti, D; Chené, A-N; Kumar, M S N; Caratti o Garatti, A; et al.
ABSTRACT: The decade-long Vista Variables in the Via Lactea (VVV) survey has detected numerous highly variable young stellar objects (YSOs). We present a study of 61 highly variable VVV YSOs (Δ Ks = 1–5 mag), combining near-infrared spectra from Magellan and ESO Very Large Telescope with VVV and NEOWISE light curves to investigate physical mechanisms behind eruptive events. Most sources are spectroscopically confirmed as eruptive variables (typically Class I YSOs) but variable extinction is also seen. Among them, magnetically controlled accretion, identified by H i recombination emission (usually accompanied by CO emission), is observed in 46 YSOs. Boundary layer accretion, associated with FU Ori-like outbursts identified by CO overtone and H2 O absorption, is observed only in longer duration events (≥5 yr total duration). However, even in long duration events, the magnetically controlled accretion mode predominates, with amplitudes similar to the boundary layer mode. Shorter (100–700 d) eruptive events usually have lower amplitudes and these events are generally either periodic accretors or multiple time-scale events, wherein large photometric changes occur on time-scales of weeks and years. We find that the ratio of amplitudes in Ks and W 2 can distinguish between variable accretion and variable extinction. Several YSOs are periodic or quasi-periodic variables. We identify examples of periodic accretors and extinction-driven periodicity among them (with periods up to 5 yr) though more data are needed to classify some cases. The data suggest that dynamic interactions with a companion may control the accretion rate in a substantial proportion of eruptive systems, although star–disc interactions should also be considered.